Bartonella Bacteria in Urban Rats: A Movement From the Jungles of Southeast Asia to Metropoles Around the Globe - Kosoy, Michael; Bai, Ying (Frontiers in Ecology and Evolution, 2019)
Despite the widespread recognition of the risks of diseases transmission associated with international trade in domestic animals and movement of exotic animals, little is known about the role of rats in carrying pathogens between continents. The genus Bartonella, a highly prevalent and extremely diverse group of bacteria, includes species that are excellent sentinel organisms for evaluating the transoceanic and intra-continental movement of the pathogens carried by rats of the genus Rattus. The patterns of prevalence and diversity of Bartonella species infecting rats and their ectoparasites depend on the geographic locations within metropolitan areas of the Americas, Africa, Asia, and Europe. One of the points addressed in this review is a comparison of the diversity of Bartonella species carried by rats in their original habitats in Southeast Asia and in the cities occupied by rats recently. The establishment of rats in urban areas and their invasion of new territories can have significant implications for human health.